Nekustamā īpašuma tirgus attīstība Latvijā - Derevjanniha, Oļesja (Latvijas Universitāte, 2007)
Diplomdarbā „Nekustamā īpašuma tirgus attīstība Latvijā” mērķis ir izanalizēt Latvijas nekustamā īpašuma tirgu, tā attīstības ietekmējošos faktorus un attīstības iespējas nākotnē. Nekustamais īpašums jebkurā valstī, tātad arī Latvijā, ir viens no praktiski katra iedzīvotāja normālas eksistences elementiem, un notiekošais nekustamā īpašuma tirgū, it īpaši cenu svārstības, skar gandrīz katru. Darbs sastāv no ievada, 3 nodaļām, secinājumiem, priekšlikumiem un pielikumiem. Ievadā ir aprakstīts darba mērķis, uzdevumi, pētīšanas metodes, darba teorētiskā nozīme un darba praktiskā nozīme. Pirmajā nodaļā tiek pētīta nekustamā īpašuma tirgus un investīciju kopsakarība. Otrajā nodaļā pētīti nekustamā īpašuma tirgus attīstību ietekmējošie faktori. Trešajā nodaļā analizētas Latvijas nekustamā īpašuma tirgus attīstība un perspektīvas. Darbs apjoms ir 91 lapas., tajā ir 8 attēli, 9 tabulas un 1 pielikums. Darba veikšanai izmantoti 55 literatūras avoti.

The purpose of this thesis “Development of the Real Estate Market in Latvia” is to evaluate situation on Latvian realty market, factors influencing its development, and potential of market development in future. Real estate is a constituent of normal existence of each inhabitant of any country, so is in Latvia. Thus, situation on real estate market, especially price fluctuations, influences everyone. The work consists of introduction, three chapters, conclusions, offers and appendices. The introduction describes the purpose and goals of the work, methods of research, theoretical and practical value of the work. The first chapter presents a research of interrelation between investments and the real estate market. The second chapter presents an exploration of the factors, which influence development of the real estate market. The third chapter shows an analysis of future development trends of Latvian real estate market. Volume of the work is 91 pages. The are 8 images, 9 tables and 1 appendices in the work. The list of literature contains 55 sources. The purpose of this thesis “Development of the Real Estate Market in Latvia” is to evaluate situation on Latvian realty market, factors influencing its development, and potential of market development in future. Real estate is a constituent of normal existence of each inhabitant of any country, so is in Latvia. Thus, situation on real estate market, especially price fluctuations, influences everyone. The work consists of introduction, three chapters, conclusions, offers and appendices. The introduction describes the purpose and goals of the work, methods of research, theoretical and practical value of the work. The first chapter presents a research of interrelation between investments and the real estate market. The second chapter presents an exploration of the factors, which influence development of the real estate market. The third chapter shows an analysis of future development trends of Latvian real estate market. Volume of the work is 91 pages. The are 8 images, 9 tables and 1 appendices in the work. The list of literature contains 55 sources.
Development of the real estate market in Latvia
Keywords: Vadībzinātne